Where to begin? The best publications for newcomers to ethnopharmacology - Jalil, Banaz; Schultz, Fabien; Heinrich, Michael (Frontiers in Pharmacology, 2023)
Have you ever tried to enter a new field of research or to get a basic overview? Of course, we all have. However, where does one begin? This mini-review offers a concise (and certainly not comprehensive) overview on the fast-evolving field of ethnopharmacology. Based on a survey in which researchers provided feedback on the publications they find most relevant in the field and an assessment of what publications have been particularly relevant in the field, this paper offers a review of the 30 best papers and books for newcomers in the field. They cover the relevant areas within ethnopharmacology and give examples from all the core regions where ethnopharmacological research is being conducted. Different and sometimes contrasting approaches and theoretical frameworks are included, as well as publications reviewing important methods. With this basic knowledge on related fields such as ethnobotany, anthropology, fieldwork methods and pharmacognosy is also incorporated. This paper is an invitation to explore fundamental aspects of the field and to understand the particular challenges faced by researchers newly entering this multi- and transdisciplinary field and provide them with examples of particularly stimulating research.